The Students’ Knowledge, Attitudes, and Behavior in Learning History at Pesantren Buya Hamka - Ristapawa Indra; Martin Kustati (Jurnal Madania)
This study aims to determine the implementation stage of history learning process for students at the Pesantren Buya Hamka; the stages of knowledge, attitudes, and behavior of students regarding nationalism and patriotism; and the correlation of leadership variables, school climate, teacher performance, and pesantren culture to history learning and also to students’ knowledge, attitudes, and behavior regarding nationalism and patriotism. This study also aims to find out the significant influence of historical learning variables on knowledge, knowledge variables on attitudes and attitudes on students’ behavior. This study combines survey research quantitative approach with descriptive, correlation, and regression methods. The results show there is a significant correlation between independent variables with historical learning variables and student knowledge variables about nationalism and patriotism. Meanwhile, there is no significant correlation between independent variables and student behavior variables. The results also show only the history of learning variables among the five independent variables that significantly influence the knowledge of nationalism and student patriotism. Student knowledge variables about nationalism and patriotism partially also affect changes in student attitudes, while changes in student attitudes do not affect linearly on changes in student behavior.